The Rocky Mountains as a dispersal barrier between barn owl (Tyto alba) populations in North America. (30th March 2018) - Machado, Ana Paula; Clément, Laura; Uva, Vera; Goudet, Jérôme; Roulin, Alexandre
Abstract: Aim: Geological barriers within a species range play a key role in shaping patterns of genetic variation by restricting gene flow. Mountain ranges are particularly imposing barriers responsible for creating genetic differentiation across multiple taxa, from small amphibians to large mammals and birds. Here, we examined the population structure of North American barn owls ( Tyto alba ) and investigated whether the Rocky Mountains influence gene flow and dispersal at the continental scale. Location: Continental North America. Methods: We collected 292 museum samples covering the species range, genotyped them at 20 microsatellite markers and sequenced 410 bp of the mitochondrial gene ND6 . Population and landscape genetics tools were used to study range‐wide patterns of structure and identify gene flow barriers. Ring recapture data were also analysed to investigate individual movement patterns and frequency of exchanges between both sides of the Rocky Mountains. Results: We found faint overall genetic structure, which is consistent with barn owl's high mobility across its continuous range. Nonetheless, we identified two distinct genetic groups on the western and eastern regions of the Rocky Mountains with a likely contact point through the narrow southern pass between them and the Sierra Madre Occidental in Mexico. Accordingly, most recaptured barn owls remain on the same side of the mountains. The Rockies appear to significantly isolate the populations in the west, which, as a consequence, display lower genetic diversity than their counterparts to the east. Main conclusions: The Rocky Mountains appear to constrain barn owl dispersal and gene flow. Our study supports the hypothesis that regional landscape barriers can shape gene flow and population structure even in highly mobile organisms.